KARAKTERISTIK GEOKIMIA REMBESAN MINYAK BUMI DI DAERAH BANTAL, KECAMATAN BANCAK, SEMARANG, JAWA TENGAH GEOCHEMICAL CHARACTERISTIC OF OIL SEEPAGE IN BANTAL AREA, SEMARANG, CENTRAL JAVA - , Wahyu Pramono ([Yogyakarta] : Ikatan Ahli Geologi Indonesia, 2008)
In Bantal Area, Bancak District, Semarang Regency, Central Java Province, some oil seeps have been found. This area, which is geologically located in the western part of Kendeng Zone, is very interesting to be researched because the petroleum system in this zone still need to be discussed. Oil seepage in Bantal area indicates that there is an effective source rock which has produced hydrocarbon. The objectives of this research is to understand the composition of oil seepage, to infer the organic matter sources and the possible source rock. Geochemistry analysis has been done to obtain this objectives. Gas chromatography analysis on 3 saturated fraction sample of oil seepage shows that the distribution pattern of n-alkane are high in C8-C15 and C25-C28 , whereas the Pristane/Phytane (Pr/Ph) ratio are &gt